Pengaruh Personal Background, Pengetahuan Dewan Tentang Anggaran, dan Political Culture terhadap Peran DPRD dalam Pengawasan Keuangan Daerah - Wibowo, Sigit Arie (Journal of Accounting and Investment, 2012)
This research aim to examine the influence of personal background, council budget knowledge, and political culture towards the role of DPRD on region financial control. This research is motivated by the fact that individual background will effect to individual behaviour on political activity. The data in this research consist of primary data that taken from questionaries distributed directly to respondents. The collected are from 144 members of DPRD at Karesidenan Cirebon. Hypothesis of this research are examine by using independent t test, Analysis of Variance (ANOVA), and multiple regression. The result of this research in general shows that personal bacground and political culture have no significant influence towards the role of DPRD on region financial control. But, the council budget knowledge has significant influence towards the role of DPRD on region financial report.